Hemostatic markers in ischemic stroke of undetermined etiology - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
To evaluate the role of the coagulation and fibrinolysis abnormalities in the pathogenesis of ischemic stroke of undetermined etiology, we assayed plasma concentration of fibrinopeptide-A and thrombin-antithrombin III complex, both sensitive markers for thrombin activation and fibrin formation, and D-dimer, a marker of plasmin activity and fibrinolysis, Hemostatic markers were measured in 32 patients with acute stroke and 20 patients with chronic stroke, and compared with 21 normal subjects. Fibrinopeptide-A and thrombin-antithrombin III complex levels were not elevated significantly, whereas the D-dimer level was markedly raised in acute (p<0.001) and chronic (p<0.05) phases of ischemic stroke in comparison with the control group. Prolonged elevation of D-dimer concentration suggests that hemostatic abnormalities have a primary role in the pathogenesis of ischemic stroke. The measurement of D-dimer concentration may help to better decide the indications for therapy of the patients with ischemic stroke of undetermined etiology. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: fibrinopeptide-A; thrombin-antithrombin III; D-dimer; hemostasis; ischemic stroke; COAGULATION; FIBRINOLYSIS; ABNORMALITIES; THROMBOSIS; ACTIVATION; PLASMA; SYSTEM; PHASES